On safe sets of the Cartesian product of two complete graphs - Kang, Bumtle; Kim, Suh Ryung; Park, Boram (Ars Combinatoria, 2018)
Fujita et al. [3] introduced the notions of safe number and connected safe number in connection with a variation of the facility location problem. In this paper, we compute the safe number and the connected safe number of Cartesian product of two complete graphs, keywords. Safe set; Connected safe set; Safe number; Connected safe number; Cartesian product; Complete graph.